The utilizing of zeolite and manures for increasing potassium availability, uptake, and yield on soybean in Alfisols. (October 2019) - Haniati, I L; Minardi, S; Nastiti, A H L; Harieni, S; Syamsiyah, J; Hartati, S
Abstract: Enhancement soybean production is needed to fulfill its high demand in Indonesia by utilizing the widespread potential land, such as Alfisols. Zeolite and manure addition used to overcome the nutrient availability in Alfisols and decrease the use of inorganic fertilizer. This study was conducted in field condition in a factorial randomized complete block design with three replicates in an Alfisols aimed to assess the effect of applying three rates of zeolites (Z0: 0 t.ha −1, Z1: 2.5 t.ha −1 and Z2: 5 t.ha −1 ) and three types of 5 t.ha −1 manures (P0: 0 No Manure, P1: quail manure (5 t.ha −1 ), P2: cattle manure (5 t.ha −1 )) on K availability, its uptake, number of pods and seed weight/plot on soybean [ Glycine max. (L) Merrill ]. Zeolites showed a significant result of potassium availability at the rate 5 t.ha −1 . The similar result is given by cattle manure for potassium uptake in soybean. An interaction between zeolites at the rate 5 t.ha −1 and cattle manure showed the significant result on a number of pods.plant −1, 100-seeds weight and seed yield.